Endoscopic Endonasal Excision of Nasal Meningoencephalocele with Repair of Skull Base Defect in 2-years 4-month-Old Child: A Case Report (Pulse, 2025)
Nasal menigoenchephalocoeles are herniation of cranial content through a bony defect in the anterior skull base into the nasal cavity. Clinical presentation includes unilateral nasal mass, nasal obstruction, rhinorrhea, and recurrent meningitis. These lesions are treated surgically as soon as possible to prevent meningitis and to address symptoms such as nasal obstruction, and cerebrospinal fluid (CSF) rhinorrhea. With the advent of endoscopic skull base approaches and instruments, surgical treatment of nasal menigoenchephalocoeles has transitioned from large bi-coronal external approaches to more minimally invasive endonasal endoscopic approaches, even though it is safe in pediatric patients. Here we report a 2-years 4-month-old child with nasal meningoencephalocele with CSF leak who was managed nasoendoscopically and had good outcome.Pulse Volume 16, Issue 2 2024: 51-55